Spectrum of acute, recurrent and chronic pancreatitis in children - Muhammad Imran; Sabeen Abid Khan; Munir Iqbal Malik (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To determine the clinical presentation, aetiology and outcome of pancreatitis in paediatric population. Method: The retrospective study was conducted at Shifa International Hospital, Islamabad, Pakistan, and comprised data of children with pancreatitis presenting between 2013 and 2018. Medical records were reviewed and findings of clinical, laboratory workup and management were noted on a specifically developed proforma. Data was analysed using SPSS 23. Results: Of the 51 subjects, 28(54.9%) were boys. The overall mean age was 10.6+4.9 years. The most frequent clinical symptom was epigastric pain 39(76.5%). The most common aetiology was gallstones/pancreatic stones 19(37.25%). Mean hospital stay was 5.1± 1.8 days, and it was longer in children aged up to 5 years compared to older children (p<0.05). Acute pancreatitis was seen in 23(45.09%) patients, followed by recurrent 19(37.25%) and chronic 9(17.64%). There was no mortality. Conclusion: Timely diagnosis and prompt management of hemodynamic status could lead to successful recovery without any serious complications in paediatric pancreatitis. Continuous...